The thyroid receptor modulator KB3495 reduces atherosclerosis independently of total cholesterol in the circulation in ApoE deficient mice - Mörk, L.; Rehnmark, S.; Davoodpour, P.; Norata, Giuseppe; Larsson, L.; Witt, M.; Malm, J.; Parini, P. (Public Library of Science, 2013)
Background: Thyroid hormones (TH) regulate cholesterol metabolism but their use as lipid-lowering drugs is restricted due to negative cardiac effects. TH mimetic compounds modulating TH receptor ß (THRß) have been designed as potential drugs, reducing serum cholesterol levels while avoiding apparent deleterious cardiac effects. Objective: Using ApoE deficient mice, we examined whether KB3495, a TH mimetic compound, reduces atherosclerosis and if there is a synergistic effect with atorvastatin. The effect of KB3495 was investigated after 10 and 25 weeks. Results: KB3495 treatment reduced atherosclerotic plaque formation in aorta and decreased the cholesteryl ester (CE) content by 57%. Treatment with KB3495 was also associated with a reduction of macrophage content in the atherosclerotic plaques and reduced serum levels of IL-1ß, TNFalpha, IL-6, Interferon ?, MCP-1 and M-CSF. Serum lipoprotein analysis showed no change in total cholesterol levels in ApoB-containing lipoproteins. KB3495 alone increased fecal BA excretion by 90%. The excretion of neutral sterols increased in all groups, with the largest increase in the combination group (350%). After 25 weeks, the animals treated with KB3495 showed 50% lower CE levels in the skin and even further reductions were observed in the combination group where the CE levels were reduced by almost 95% as compared to controls. Conclusion: KB3495 treatment reduced atherosclerosis independently of total cholesterol levels in ApoB-containing lipoproteins likely by stimulation of sterol excretion from the body and by inhibition of the inflammatory response. © 2013 Mörk et al.